A review on the recent mechanisms investigation of PFAS electrochemical oxidation degradation: mechanisms, DFT calculation, and pathways - Li, Gengyang; Peng, Mason; Huang, Qingguo; Huang, Ching-Hua; Chen, Yongsheng; Hawkins, Gary; Li, Ke (Frontiers in Environmental Engineering, 2025)
Per- and polyfluoroalkyl substances (PFAS) have drawn public concern recently due to their toxic properties and persistence in the environment, making it urgent to eliminate PFAS from contaminated water. Electrochemical oxidation (EO) has shown great promise for the destructive treatment of PFAS with direct electron transfer and hydroxyl radical (⋅OH)-mediated indirect reactions. One of the most popular electrodes is Magnéli phase titanium suboxides. However, the degradation mechanisms of PFAS are still unsure and are under investigation now. The main methodology is the first-principal density functional theory (DFT) computation, which is recently used to explore the degradation mechanisms and interpret by-product formation during PFAS mineralization. From the literature review, the main applications of DFT computation for studying PFAS degradation mechanisms by EO include bond dissociation energy, absorption energy, activation energy, and overpotential η for oxygen evolution reactions. The main degradation mechanisms and pathways of PFAS in the EO process include mass transfer, direct electron transfer, decarboxylation, peroxyl radical generation, hydroxylation, intramolecular rearrangement, and hydrolysis. In the recent 4 years, 11 papers performed DFT computation to explore the possible PFAS degradation mechanisms and pathways in the EO process. This paper’s objectives are to: 1) summarize the main degradation mechanisms of PFAS degradation in EO; 2) review the application of DFT computation for studying PFAS degradation mechanisms during EO; process; 3) review the possible degradation pathways of perfluorooctane sulfonoic acid (PFOS) and per-fluorooctanoic acid (PFOA) during EO process.